2009
DOI: 10.1109/tcbb.2008.135
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Approach for Reconstructing Ancient Gene Clusters

Abstract: The order of genes in genomes provides extensive information. In comparative genomics, differences or similarities of gene orders are determined to predict functional relations of genes or phylogenetic relations of genomes. For this purpose, various combinatorial models can be used to identify gene clusters--groups of genes that are colocated in a set of genomes. We introduce a unified approach to model gene clusters and define the problem of labeling the inner nodes of a given phylogenetic tree with sets of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…To detect all conflicts, it is sufficient to find the minimal conflicting sets, a general notion that was used to deal with inconsistency in reconstructing ancestral genomes [26,27]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect all conflicts, it is sufficient to find the minimal conflicting sets, a general notion that was used to deal with inconsistency in reconstructing ancestral genomes [26,27]. …”
Section: Methodsmentioning
confidence: 99%
“…Remark: General, but exponential time, techniques were described in [26,27], for the different problem of reconstructing ancestral genomes and gene clusters, but they can be applied for deletion clusters. As far as we know, ad-hoc approaches for the specific case of deletion clusters have not been investigated.…”
Section: Appendix A: Statements Of Algorithmic and Combinatorial Optimentioning
confidence: 99%
“…The notion of Minimal Conflicting Set was introduced to handle non-C1P binary matrices and false positives in [3] and [28]. If a binary matrix M does not have the C1P, a Minimal Conflicting Set (MCS) is a submatrix M ′ of M composed of a subset of the rows of M such that M ′ does not have the C1P, but every proper subset of rows of M ′ has the C1P.…”
Section: Such Ordering Of the Markers Define Chromosomal Segments Calmentioning
confidence: 99%
“…For example, the algorithm of Stoye and Wittler [28] described in Section 2 is a satisfiability oracle based algorithm -it uses a polynomial-time oracle to decide if a given submatrix has the C1P, but it doesn't use this structure any further. Once it has found the complete list C of MCS, it will proceed to check all MC1PS sets as candidate conflicting sets before terminating.…”
Section: Theorem 4 [15]mentioning
confidence: 99%
“…Recent research in comparative genomics has proved MCS to be of particular interest. Indeed, Bergeron et al [2] and Stoye et al [25] have shown how to compute parsimonious evolution scenarios of gene clusters by ranking rows according to their Conflicting Index (CI), i.e., the number of MCSR involving a row. In both papers, the problems of efficiently computing the CI of a row and of generating all the MCS of a matrix problems were explicitly raised.…”
Section: Introductionmentioning
confidence: 99%